Experimental protocol for sea level projections from ISMIP6 stand-alone ice sheet models - Nowicki, Sophie; Goelzer, Heiko; Seroussi, Helene; Payne, Anthony J.; Lipscomb, William H.; Abe-Ouchi, Ayako; Agosta, Cecile; Alexander, Patrick; Asay-Davis, Xylar S.; Barthel, Alice; Bracegirdle, Thomas J.; Cullather, Richard; et al. (The Cryosphere, 2021)
Donald Slater acknowledge support from NSF (grant no. 1916566) and NASA (grant no. NNX17AI03G). Projection of the contribution of ice sheets to sea level change as part of the Coupled Model Intercomparison Project Phase 6 (CMIP6) takes the form of simulations from coupled ice sheet-climate models and stand-alone ice sheet models, overseen by the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). This paper describes the experimental setup for process-based sea level change projections to be performed with stand-alone Greenland and Antarctic ice sheet models in the context of ISMIP6. The ISMIP6 protocol relies on a suite of polar atmospheric and oceanic CMIP-based forcing for ice sheet models, in order to explore the uncertainty in projected sea level change due to future emissions scenarios, CMIP models, ice sheet models, and parameterizations for ice-ocean interactions. We describe here the approach taken for defining the suite of ISMIP6 stand-alone ice sheet simulations, document the experimental framework and implementation, and present an overview of the ISMIP6 forcing to be used by participating ice sheet modeling groups. Peer reviewed